How Changes in the Aesthetics of Representation and Cubism Affected Gertrude Stein’s Libretto “Four Saints in Three Acts” - Zeynep Erdal; Aslıhan Ünlü (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
This article aims to analyze Gertrude Stein’s libretto, “Four Saints in Three Acts” through the perspective in Picasso’s cubist landscape paintings. The transformation Stein made to the aesthetics of representation was inspired by Picasso’s cubist landscape paintings and affected her writing style. To understand these new aesthetics, the study will first focus on how the way seeing had changed through Cubism and Picasso’s cubist landscape techniques, analyzing the multi-perspective Picasso used in cubist painting as the principle indicator of this technique. The study will then focus on how Stein applied this technique to her writing. Stein is seen to have used every kind of possible argument make language performative in her work, such as rhythmically repeating words and employing homonyms and homophones, thus using the multi-perspective technique as suggested by cubic painting to form her libretto “Four Saints in Three Acts”.